2020
DOI: 10.1111/jam.14606
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of essential oils from Asteraceae plant against pathogenic fungi of Panax notoginseng

Abstract: Aims Diseases caused by pathogenic fungi was a major constrain in increasing productivity and improving quality of Panax notoginseng. The aim of this research was to evaluate the inhibitory activity of essential oils (EOs) from Asteraceae family, Chrysanthemum indicum and Laggera pterodonta, against pathogenic fungi of P. notoginseng. Methods and Results The antifungal activity was investigated using multiple methods, disclosing that the EOs from C. indicum and L. pterodonta are active against hypha growth of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 28 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…Specifically, Fusarium , known for causing chrysanthemum wilting, demonstrated an increased relative abundance in the rhizosphere of chrysanthemums. This observation concurs with the findings presented by Zeng et al, who concluded that Fusarium plays a significant role in the pathogenesis of chrysanthemum wilting, and its elevated presence in the rhizosphere is indicative of a potential disease outbreak [ 26 ]. The RDA analysis results of this study indicated that soil nutrient factors exert a substantial impact on microbial composition, with pathogenic bacteria being the main influencing factor in the composition of rhizosphere bacterial community.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, Fusarium , known for causing chrysanthemum wilting, demonstrated an increased relative abundance in the rhizosphere of chrysanthemums. This observation concurs with the findings presented by Zeng et al, who concluded that Fusarium plays a significant role in the pathogenesis of chrysanthemum wilting, and its elevated presence in the rhizosphere is indicative of a potential disease outbreak [ 26 ]. The RDA analysis results of this study indicated that soil nutrient factors exert a substantial impact on microbial composition, with pathogenic bacteria being the main influencing factor in the composition of rhizosphere bacterial community.…”
Section: Discussionsupporting
confidence: 93%
“…Speci cally, Fusarium, known for causing chrysanthemum wilting, demonstrates an increased relative abundance in the rhizosphere of chrysanthemums. This nding aligns with the conclusion drawn by Zeng's team [24].…”
Section: Discussionsupporting
confidence: 91%
“…In addition to EOs of Zingiberaceae plants, Zeng et al. ( 2021 ) reported that Chrysanthemum indicum and Laggera pterodonta EOs reduce root rot disease of P. notoginseng by their direct antifungal activity. Ma, Chen, Li, Wang, et al.…”
Section: Biological Control Of Root Rot In P Notoginsengmentioning
confidence: 99%